METODE AL-QUR’AN DALAM MENTRANSFORMASI PEPERANGAN MENJADI PERDAMAIAN (Reintrepretasi Ayat-Ayat Pedang Berbasis Analisis Tartib Nuzuli) - Muhammad Alwi HS; Afrida Arinal Muna; Husnul Khotimah (Jurnal Ilmiah Ilmu Ushuluddin, 2020)
This article re-discusses the verses related to war, this is based on the assumption that Islam, which is blessed by nature, certainly has a background in the existence of war issues recorded in the Qur'an. So much so that through this writing, will refute and reverse the understanding that the Qur‟an was originally understood as a text of radical and war, into a text that demands peace for all mankind. This article analyzes the verses of war by using the method of nuzuli order, which is to understand the Qur'an based on the descending order of the verses. The results of this article state that the emergence of war verses in the Qur‟an is the Qur‟an‟s response to the issue of war in the tradition of Arab society, known as the story of ayyam al-Arab. In the three great wars: the Battle of Badr, Uhud, Khandaq, the Qur‟an has always guided Muslims in waging war. In the battle of Badr, Muslims were instructed not to start a war, done with sincerity, with intention for the sake of Allah. At the Battle of Uhud it was directed by the Qur‟an to eliminate slander. As for the Khandaq War, the Qur'an shows the power of Allah: about the non-occurrence of war, that it is Allah who governs the Muslims not to wage war. From here, it can be seen that the effort to expose the 'tradition' of war of the Arab Community, was transformed into peace as they became the Arab Islamic Community.